2017
DOI: 10.1002/prs.11950
|View full text |Cite
|
Sign up to set email alerts
|

Effects of external radiation heat flux on combustion characteristics of pure and oil‐impregnated transformer insulating paperboard

Abstract: The effects of external radiation heat flux on the combustion characteristics of pure transformer insulating paperboard (PTIP) and oil‐impregnated transformer insulating paperboard (OITIP) were investigated experimentally. The experiments were conducted with the cone calorimeter using five external radiation heat fluxes that ranged from 25 to 80 kW/m2. The results showed that the ignition time decreased with the external radiation heat flux, and the ignition time of PTIP was much longer than that of OITIP. Bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…To properly analyze the test results of transformers, so-called standard dependencies are necessary, and are determined for different moisture levels and temperatures of insulation. The standard dependencies, as a rule, are performed in laboratories on the basis of paper or electrotechnical pressboard dried under vacuum, humidified in air, and then impregnated with insulating oil [21][22][23][24]. In the paper [25], on the basis of analysis of the test results of moisturized paper impregnated with insulating oil, it was found that water accumulates in cellulose fibers in the form of a nanodrops with a diameter of about 2.3 nm, containing about 220 water molecules each.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To properly analyze the test results of transformers, so-called standard dependencies are necessary, and are determined for different moisture levels and temperatures of insulation. The standard dependencies, as a rule, are performed in laboratories on the basis of paper or electrotechnical pressboard dried under vacuum, humidified in air, and then impregnated with insulating oil [21][22][23][24]. In the paper [25], on the basis of analysis of the test results of moisturized paper impregnated with insulating oil, it was found that water accumulates in cellulose fibers in the form of a nanodrops with a diameter of about 2.3 nm, containing about 220 water molecules each.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1a,b on the horizontal axis show values of (f τm). Comparison of the experimental frequency dependence αmax(f) and the numerical determination α(f τm) shown in Figure 1b allows determination of the value of the expected relaxation time τm entering into Formulas (22) and (23). To do this, a relationship is chosen from a family of waveforms α(f τm) defined numerically, the maximum value for which is equal to the maximum experimental curve:…”
mentioning
confidence: 99%
“…It was found that the compression characteristics of OTIP is irrelevant to the type of oil. Using cone calorimeter, Zhang et al 15,16 studied the heat transfer and combustion characteristics of OTIP. The results show that the 0.5 mm OTIP can be regarded as thermally thin material, and the paperboard with the thicknesses of 1.5, 2.0, and 3.0 mm were thermally thick materials.…”
Section: Introductionmentioning
confidence: 99%
“…Previous researches have shown that the combustion characteristics of TIP have been obviously changed after it is impregnated by the transformer oil. However, in the existing studies, the immersion time was 48 h. [15][16][17] Under such an immersion time, the content and distribution of transformer oil in the OTIP may not reach steady state, so it cannot fully reflect the working conditions of OTIP. Therefore, in this study, firstly the OTIP with different immersion times and oil contents were prepared.…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, the pressboard is vacuum dried and then humidified in atmospheric air, where the moisture is absorbed by a dry pressboard. After moisturization, the reference sample is impregnated with transformer oil at the atmospheric pressure [34][35][36][37][38][39][40][41]. The process of pressboard moisturization in power transformers is different.…”
Section: Introductionmentioning
confidence: 99%